Optimalisasi Digital Repository Literation dalam Pembuatan Bahan Ajar Geografi Berbasis Micro Web Learning: Indonesia - Wahyudi, Adip; Mutia, Tuti; Arifin, Slamet; Hasporo, Cahyo Aji; Maulana, Feri Fahrian; Perdana Putra, Dimas Bayu; Putra, Halil Haqizul (Politeknik Piksi Ganesha Indonesia, 2025)
Digital technology is becoming increasingly important in the field of education, especially in the context of 21st-century learning challenges. However, in the Madura region, the implementation of technology in geography teaching still faces many obstacles. The digital literacy of teachers is still relatively weak. This study aims to enhance the digital knowledge of geography teachers in the MGMP (Subject Teacher Group) in Madura through learning materials based on micro web learning. The community service program was conducted through training and mentoring to enable teachers to access, manage, and integrate digital resources into their teaching. The results show a significant improvement in teachers' digital skills, which positively impacted the quality of teaching and student motivation. However, challenges such as limited technological infrastructure and the need for continuous training remain. This study concludes that improving the digital literacy of geography teachers can enhance the quality of education in Madura with the right strategies. Recommendations include collaboration between the government, schools, and educational communities to improve infrastructure and provide continuous training.